Pengaruh Budaya Organisasi, Beban Kerja dan Kompensasi Terhadap Produktivitas Kerja Karyawan Pada PT. Unggul Widya Teknologi Lestari Kabupaten Mamuju Tengah - Esterata Lede, Mayomi Reta; Ramadhan, Adam (Journal of Management Branding, 2026)
This study aims to determine the effect of organizational culture, workload, and compensation on employee work productivity at PT. Unggul Widya Teknologi Lestari in Central Mamuju Regency. A good organizational culture is expected to improve work motivation, while a balanced workload and fair compensation are expected to encourage employees to work more productively. The research method used is a survey with a quantitative approach, and data were collected through questionnaires distributed to 98 employees of PT. Unggul Widya Teknologi Lestari. Data analysis was performed using multiple linear regression to determine the extent to which the three independent variables (organizational culture, workload, and compensation) affect the dependent variable, which is employee work productivity. The results show that organizational culture, workload, and compensation simultaneously have a significant effect on employee work productivity. Partially, organizational culture has a significant positive effect on work productivity, as does workload and compensation. However, excessively heavy workload can decrease work productivity, while adequate compensation can improve employee motivation and performance. This study provides important implications for company management to pay more attention to organizational culture, workload management, and providing appropriate compensation to enhance employee work productivity